MODERN THREATS TO THE FINANCIAL SECURITY OF THE ENTERPRISE - Butkevych, Taras (Український економічний часопис, 2024)
Introduction. In recent years, the need to secure financial stability has become increasingly critical, spanning from the broader macroeconomic scale down to businesses and individual households. This concern remains a major and highly relevant issue, especially in the context of Ukraine's currently unstable economic climate.Purpose. The article aims at identifying the main threats to the financial security of enterprises and developing recommendations for their elimination. Methods. The article uses the methods of analysis and synthesis to determine the main parameters of external and internal threats to the financial security of enterprises, and abstract methods to make theoretical generalizations and conclusions of the study. Results. The article summarizes a research study on the primary threats to a business's financial security. It delves into the various components and structural elements that constitute an enterprise's financial security. The study also outlines strategies to mitigate these threats, focusing on the integration of key subsystems that collectively form a comprehensive approach to managing financial security. This integrated system encompasses strategic management of financial security, financial analysis and control, optimization of financial processes, investment policy, and the management of liquidity and risks. Conclusion. Analyzing and categorizing threats to financial security based on their functional components offers a pathway to develop targeted strategies that enhance both the specific components and the overall financial security of an enterprise. It's crucial to recognize that the array of threats can differ greatly between different enterprises. To safeguard a company's financial security in today's economic climate, it's essential to classify these threats based on various factors: their origin, area of impact, likelihood of occurrence, duration of effect, and severity. This detailed identification is a critical step in making informed decisions to mitigate the adverse effects on the financial health and ongoing economic stability of the business.